(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to observe effluent management technique, physico-chemical characteristic (BOD, TDS, DO, pH, EC, temperature, color, odor, transparency and heavy metals) at different steps of effluent treatment process and compare those with standards of Bangladesh Environmental Conservation Rules (ECR)-1997. Nine effluent samples were collected from Impress Newtex Composite Textile Ltd Industries at Gorai under Mirzapur Upazila during the month of January to June 2013. The color and odor of the inlet effluent samples were highly colored and emit foul smell, respectively but in case of outlet effluent samples very low. The DO, BOD, TDS, EC, pH, temperature, transparency value of all collected samples from ETP outlet were 5 mg/l, 42 mg/l, 2245 mg/l, 192 ?s/cm, 6.5, 31.2 cm, respectively which fulfils ECR (1997) standards for inland surface water, public sewerage water and land for irrigation excepts the value of TDS. In case of heavy metal (Pb, Zn &Ni) assessment the concentrations of all collected samples were within the permissible limit according to ECR, 1997 accepts Pb for inland surface water and land for irrigation. Different types of dyes and chemicals were used during fabrics dyeing. As a result, the values of different physico-chemical parameters were more in inlet effluent but due to treatment its shows less value at the outlet effluent which fulfils ECR (1997) standards requirement. Only best management practices can ensure the best effluent quality discharged into the environment as well as best performance of ETP. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22204 J. Environ. Sci. & Natural Resources, 7(2): 53-58 2014